R&D investments and quality of life in Turkey - Erdin, Ceren; Ozkaya, Gokhan (ELSEVIER SCI LTD, 2020)
The standards of development and life quality of cities play an important role in the investment and career planning of the investors and the qualified people who will work in R&D and Technoparks. Also, all the leading cities in the world are the most developed cities in the regions and countries in terms of R&D and innovation. Therefore, all cities in Turkey are compared by using the R&D investment data and TurkStat Quality of Life Index for Cities. The criteria are weighted by the Fuzzy Analytic Hierarchy Process (FAHP). Then 81 cities are compared with the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The article aims to provide information about the current situation of Turkey's cities regarding R&D, Technology Development Zones and quality of life. According to the results, the quality of life and socio-economic development has a very close relationship with the existence of R&D investments. If the current development policy continues, the regions with low quality of life will continue to lag behind the other cities in terms of development. The study indicates that there are remarkable differences between eastern and western Turkey in terms of living standards and the contribution of R&D and Technoparks to economic development.
Keywords: Regional development; Research and development; Economic inequality; Fuzzy analytic hierarchy process; TOPSIS; Quality of life; Turkey; Inequality; Public economics; Economic development; Economic growth; Employment; FUZZY; INDICATORS; AHP; Science & Technology - Other Topics